Accurate and Efficient Approximate Quasiparticle DFT‐1/2 Band Structure Calculations of Transition Metal Oxide Perovskites. Issue 6 (15th April 2022) - Yagui, Lucas; Guilhon, Ivan; Marques, Marcelo; Teles, Lara K.
Abstract : The transition metal oxide perovskites are materials intensively studied due to their diversity of chemical and physical properties, as well as their potential for wide applications. From the theoretical point of view of ab initio calculations of quasiparticle (QP) energies and band structures, they remain a challenge. Herein, the performance of the low computational cost ab initio DFT‐1/2 approximate QP method is assessed for the nonmagnetic transition metal oxide perovskites, including 3 d SrTiO 3, LaScO 3, 4 d SrZrO 3, and 5 d KTaO 3 and SrHfO 3 . The results with experiments and a large set with other QP calculations are compared. It is demonstrated that the DFT‐1/2 method presents a remarkable accuracy for these materials, opening an avenue to study more complex systems. Abstract : The low computational cost DFT‐1/2 method for approximate quasiparticle corrections is applied for the calculation of electronic structures of a set of nonmagnetic transition metal oxide perovskites. A detailed comparison with other methods and the experimental data shows a remarkable performance of the method, opening an avenue for the study of more complex systems as, e.g., heterostructures and alloys.